SURGICAL OUTCOMES OF ACCESSORY NAVICULAR IN ADOLESCENT ATHLETES. Issue 7 (30th July 2021) - Yang, A; Hennrikus, WL.; Bone, Penn State Hershey Pediatric; ,; Hershey, PA
Introduction: An accessory navicular (AN) is a plantar medial enlargement of the navicular bone of the foot. Patients with AN present with a foot bump. Only some patients are symptomatic with pain. The purpose of this study is to report the surgical outcomes in a consecutive series of adolescent athletes with symptomatic AN. Methods: The study was approved by the College of Medicine IRB. 16 patients were evaluated. Patient gender, age, complaints, family history, sports played, conservative treatments attempted, duration of symptoms, surgical technique, complications, outcomes, average follow up, time to return to normal activity, # that returned to sports, and the time to return to sports were recorded. Radiographs were used to identify the type of AN (Coughlin system), skeletal maturity, and presence of pes planus. Pes planus was determined by standing lateral foot radiograph talo-first metatarsal angle. Results: 16 patients and 17 feet were studied. 15 were female (94%). The average age at surgery was 13 years (range 10 to 18 years). 0 patients had a family history of AN. The presenting complaint was foot pain and a bump. Sports including 2 basketball, 2 cheer, 4 gymnastics, 3 soccer, 1 volleyball, 1 dance, 1 softball, 2 multiple sports. The average duration of symptoms was 22 months (range 1 to 36 months). Conservative care methods attempted included: shoe inserts, activity modification, anti-inflammatory medications, icing, crutches, and changes in footwear. Pre-op radiographs demonstrated 9 Coughlin Type 1, 3 Type 2, and 5 Type 3 AN's. Pre-op radiographs demonstrated 8 feet (47%) had flat foot. 9 feet (53%) had fused the calcaneal growth plate. All patients had a simple excision of the AN and 13 feet (76%) had an additional reefing of the posterior tibial tendon. The average time to return to normal activities was 13 weeks (range 8 to 16 weeks). 15/16 patients (94%) were able to return to their pre surgery sports. The average follow-up time was 8.5 months. At final follow up, 13 feet (76%) reported no pain, 3 (18%) with minimal pain, and 1 (6%) with no change in pain. No complications were reported. Discussion and Conclusion: Symptomatic AN is more common in females. Surgical success was unrelated to a closed growth plate. Surgery eliminated pain in 76% of patients and allowed 94% of patients to return to sport. Residual pain in 4 patients was correlated with a pre-op flat foot (4/8 patients: 50%).